Plant Diversity and Evolution: Genotypic and Phenotypic Variation in Higher Plants 2004
DOI: 10.1079/9780851999043.0201
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in plant cell walls.

Abstract: This chapter compares the components and structures of dicotyledon cell walls, monocotyledon cell walls, Peridophyte cell walls and gymnosperm cell walls. The evolution of cell walls is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
76
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 0 publications
3
76
0
Order By: Relevance
“…The presence of fucosylated XyGs in Nicotiana pollen grains and tubes was consistent with the immunofluorescence labelling pattern seen with the monoclonal antibody CCRC-M1, which binds terminal Fuc residues linked α-(1,2)- to a galactosyl residue, the epitope found in the F side chain of XyG [42,43] and with other studies of Arabidopsis pollen grains and pollen tubes where fucosylated XyGs are also found [38,43]. However, although XXFG and XLFG are XyG structures found in many dicot cell walls (e.g., see 44), fucoslyated XyGs are not expected in a solanaceous plant like Nicotiana , where previous studies of the XyGs in vegetative tissues have found less Xyl substitution (a XXGG core structure instead of the more usual XXXG) and no Fuc residues [45,46]. Instead of Fuc, the XyG side chains in the Solanaceae have Ara residues attached to some of the Xyl [45].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The presence of fucosylated XyGs in Nicotiana pollen grains and tubes was consistent with the immunofluorescence labelling pattern seen with the monoclonal antibody CCRC-M1, which binds terminal Fuc residues linked α-(1,2)- to a galactosyl residue, the epitope found in the F side chain of XyG [42,43] and with other studies of Arabidopsis pollen grains and pollen tubes where fucosylated XyGs are also found [38,43]. However, although XXFG and XLFG are XyG structures found in many dicot cell walls (e.g., see 44), fucoslyated XyGs are not expected in a solanaceous plant like Nicotiana , where previous studies of the XyGs in vegetative tissues have found less Xyl substitution (a XXGG core structure instead of the more usual XXXG) and no Fuc residues [45,46]. Instead of Fuc, the XyG side chains in the Solanaceae have Ara residues attached to some of the Xyl [45].…”
Section: Discussionsupporting
confidence: 87%
“…However, although XXFG and XLFG are XyG structures found in many dicot cell walls (e.g., see 44), fucoslyated XyGs are not expected in a solanaceous plant like Nicotiana , where previous studies of the XyGs in vegetative tissues have found less Xyl substitution (a XXGG core structure instead of the more usual XXXG) and no Fuc residues [45,46]. Instead of Fuc, the XyG side chains in the Solanaceae have Ara residues attached to some of the Xyl [45]. The major XyG structures expected in Nicotiana are thus XSGG (where S is Ara-(1,3) Xyl) and XXGG [10,47], neither of which was found in pollen grains and tubes (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…In order to select the appropriate specificity of enzymes required for biomass degradation, we briefly summarize the occurrence of ferulic and hydroxycinnamic acids in the different types of plant biomass. A variety of hydroxycinnamic acids are present in the plant cell walls (up to 3% of cell wall dry weight), usually esterified or etherified to the polymers within the lignocellulosic matrix [14, 15]. Ferulic acid (ferulate, 4-hydroxy-3-methoxycinnamic acid, mainly trans - or E -form; Fig.…”
Section: Introductionmentioning
confidence: 99%
“…However, up to now there is still no identification of which polysaccharides ferulic acid is linked to in gymnosperms [14]. …”
Section: Introductionmentioning
confidence: 99%
“…The composition of the matrix varies depending on the cell type, stage of development and plant taxon [7, 8]. Much of what is known about the compositions of mature primary cell walls of eudicotyledons comes frequently from cell-wall preparations derived mostly from parenchyma cells.…”
Section: Introductionmentioning
confidence: 99%